Alinhavando saberes e práticas, tecendo possíveis : o trabalho em rede na assistência social - Araujo, Vivianni Barcellos de (2015)
As weavers of bobbin lace, we have investigated the work in the network of social services in an attempt to highlight the various lines that form this labor plan. We intended a research-intervention study, making records in the Field Diary, dwelling institutional sheltering spaces for children and adolescents in the city of Vitória, aiming to explore experiences produced in the work of technical and social educators, and conducting conversation circles with those who live or have lived the reality of working in the network of social assistance, what we called collectivessieves. Our meetings aimed to the incarnate word on experience, allowing the emergence of affects, assemblages and recognition of the lived. We started our lace with what we called WIRE WORK: knowing the work of professionals that form the network of social assistance services, we were able to analyze the relationships that have been updated in daily life of such services. In our journey of research, we realized that many advances have been achieved and that the construction of a truly "public" policy is made collectively, in the villus that set up the network. Thus, we brought as another wire the WIRE SUAS NETWORK, tacking and questioning the implementation of the Sistema Único de Assistência Social (SUAS), their trajectories and social technologies operationalized every day. Analyzing the inventive processes of workers, we believe that the creation of work collectives can enable an increase of power of the workers and users’ life and the network of social assistance itself, thought of as a "hot network", that is, gestated in the sensitive dimension of affections and otherness, which effectively make the public.